Medicinal properties of pomegranate - Boriyev Hakim Avazivich (Zien Journals, 2022)
There is a lot of information about pomegranate fruit and peel. The benefits of pomegranate fruit that we love to eat for the human body and its chemical composition allow us to expand the scope of use of pomegranate. In the food industry, pharmaceuticals , the need for biologically active substances derived from pomegranate fruit and peel in the chemical industry is growing day by day.
Keywords: Ascorbic acid; pomegranate peel; carotene; baking soda